Strategic management plan for GFC Quality Workers' Cooperative (GFCQWC) - Como, Myra C.; Soledad, Miguel D.; Durana, Annalee D. (Davao City School of Management, University of the Philippines Mindanao, 2007)
The GFC Quality Workers Cooperative, a primary, non-agricultural and multipurpose cooperative was organized by the regular employees of Global Fruits Corporation in 1999. The cooperative is located n Kipalbig, Tampakan, South Cotabato. Despite its less than a decade of operation, it had shown growth and profitability, much to the approval of its membership. This was largely attributed to the strong and entrepreneurial leadership which enabled them to achieve its financial gains especially in its early years and onwards. The analysis of the internal environment of the cooperative revealed a strong position in relation to its product and service portfolio which aided them to achieve high revenue. The analysis also disclosed the limited source of working capital from its member contributing to a tight cash flow. This resulted to lower revenue due to insufficient fund to cover the loan requirement. On the other hand, the external environment challenged the viability of the cooperative. Membership declined as a result of the manpower reduction program of the banana company which employs most of the members. There are indications that this will continue in the coming months, which is of much concerns to the general membership as this threatens the long-term viability of the cooperative. This strategic management plan was prepared in order to provide the cooperative with possible alternatives which they can pursue to address its growing concerns. This study revealed the external opportunities that were not explored by the cooperative in order to address its financial concerns. Recognizing the contribution of the cooperatives in the economy, there are government support programs which provide financial assistance at the lowest possible interest rate. Through the use of appropriate tools and projections conducted by the author, it is proposed that the cooperative should aggressively undertake the option of securing external financing facilities. The author believes that the use of external financing as alternative source of fund would strengthen the financial condition and profitability of GFCQWC. The cooperative should not limit its capacity to equity financing which is costlier compared to debt financing. The returns will also improve its operational efficiencies as a result of projected higher turnover of loan availment due to availability of funds. On the other hand, the cooperative has to review its credit policy to improve its collection days which is important to maintain a positive working capital. Though the GFCQWC may have been successful in its pursuit of business opportunities, the author highly recommends that they also value the importance of the overall soundness of their financial condition to ensure a more balanced working capital. This may include addressing their aversion to debt.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, 2007
Keywords: Strategic plan